KITAB KUNING DAN TRADISI RISET PESANTREN DI NUSANTARA - Andik Wahyun Muqoyyidin (IBDA` : Jurnal Kajian Islam dan Budaya, 2014)
This article discusses the typical nomenclature of kitab kuning and the tradition of Islamic research in the archipelago. According to Bruinessen, pesantren have successfully built the great tradition in the teaching of Islam based classical books are popularly known as kitab kuning. Be a strong institutional tradition of study and research, pesantren will make a major contribution in responding to contemporary issues and future. Pesantren research tradition rooted in social history, sources of value, and intellectual traditions.